Determining the Impact of Enclosure on some Indicators of Ecosystem in El-Bayadh Region, North-West Algerian Steppe, Algeria - Nora , Salemkour; Warda , Chaib; Farida , Bettiche; Haroun , Fadlaoui (Emerging Issues in Environment, Geography and Earth Science Vol. 8, 2024)
The purpose of this study is to evaluate the impact of enclosure as a technique for the restoration of degraded rangelands on plant community structure in El-Bayadh (North West Algerian steppe). Protection of degraded rangelands is widely considered to be the most effective and practical way to conserve plant diversity and maintain ecosystem composition and structure. The ecology of restoration and rehabilitation is part of the possible actions more to limit the extansion of the degradation of this ecosystem and erase or mitigate the consequences but, it is necessary to know the performance of the steppe ecosystem. The quadrat point method was used. A total of 10 surveys were carried out in each stations, several indicators of ecosystem attributes such as diversity, richness, total plant cover, perennial plant cover, annual plant cover, soil surface elements cover and pastoral value were compared between enclosure and grazed areas. The findings revealed considerable positive effects of protection on the scored parameters (Increase in floristic richness and diversity, increased in plant cover and litter, decrease in stones elements and wind veil, increase in pastoral value). However, the result semphasized a negative effect of enclosure on vegetation dynamics. For the soil surface elements, the enclosure (protection) decreases the cover stones and wind veil due to the cessation of the degradation of the bedrock by wind erosion and a good fixation of the sand by the vegetation, also the fencing has allowed the increase of the litter cover which is vital for the environment, because when it is not consumed, litter favors infiltration and germination of seeds and its presence can provide "islands" of fertility where sediment and nutrients are trapped contributing to increased floristic richness and diversity in these environments. This was observed by the occurrence of the bare silty crust on the soil surface which may constitute an obstacle to water infiltration and seeds germination, for this we suggest that this parameter be retained for the opening of these aminaged rangelands (enclosure) for grazing.